Effects and perception of multimodal recontextualization in political Internet memes. Evidence from two online experiments in Austria - Bülow, Lars; Johann, Michael (Frontiers in Communication, 2023)
Internet memes are an integral part of social media communication and a popular genre for humorous engagement in political online discourses. A meme is a collective of multimodal signs that refer to each other through shared formal, content-related, and/or stance-related characteristics and can be recontextualized on different levels: (1) language, (2) mode of presentation, and (3) humor. In this paper, we examine the perceptions and effects of recontextualization in image macros—the most prominent meme sub-genre. Two between-subjects online experiments from Austria offer a holistic approach to meaning-making through multimodal recontextualization in political image macros. The first experiment explores the perception of language variety and its effects on the users’ intention to forward a humorous image macro. The second experiment further investigates effects of a political message’s language variety, mode of presentation, and humor on users’ perceptions and behavioral intentions. The experiments’ results indicate that perceptions and behavioral intentions are mainly affected by a political message’s presentation as image macro while the recontextualization of language variety and humor plays a minor role. The study contributes to the growing body of knowledge on Internet memes as multimodal and recontextualizable political messages from the receivers’ point of view.